A social work re-reading of students as consumers. Issue 5 (4th July 2017) - Todd, Sarah; Barnoff, Lisa; Moffatt, Ken; Panitch, Melanie; Parada, Henry; Strumm, Brianna
Abstract: The concept of student as consumer highlights significant shifts in what Canadian students pay for their education and how this transition has shaped their relationship with learning as well as their overall expectations for, and participation in, the project of higher learning. Consumerism in social work education reflects broader trends towards academic capitalism in Canadian universities and is a result of neoliberal ideology reshaping higher education. In this paper, we explore student and faculty participants' reflections on the impact of consumerism on progressive social work education, exploring how participants use the term to make sense of their experiences and how doing so reshapes progressive social work education itself.